Eficiencia de la retranslocación foliar de macronutrientes en plantaciones de Vochysia lomatophylla “quillosisa” de diferentes edades en Puerto Almendra, Loreto-Perú, 2023 - Shapiama Murayari, Paul Anderson (2024)
Retranslocation consists of the reabsorption of nutrients from the leaves to the branches before leaf abscission; to avoid their loss, this becomes a nutrient conservation mechanism, which will then be redistributed, and the efficient use of the nutrient is the measure. that evaluates the repeated use of the same nutrient units. The plantations of Vochysia lomatophylla “quillosisa” of different ages have been studied at the Puerto Almendra Forestry Research and Teaching Center, in the Loreto region, with the objective of quantifying the retranslocation and efficiency in the use of nutrients, the methodology has been applied proposed by (Mendoza et al., 2014, p.1) and Vitousek, 1982, mentioned by (Del Arco et al. 1991). It has been found that the species under study carries out retranslocation of nutrients K (70.97%), >Mg (43.18%)>P (26.79%), > N (14.35%), > Ca (12.30), with negative retranslocation for sulfur and Regarding the efficient use of nutrients, it has been found Mg (2458.33 Kg/ha-1) > P (1875.00 Kg/ha-1), > K(894.89 Kg/ha-1), > S(841.86 Kg/ha-1) , >Ca (308.56 Kg/ha-1), > N (72.68 Kg/ha-1). There is no significant difference in the age range between 24 and 45 years. The species Vochysia lomatophylla “quillosisa” can be incorporated into models of restoration and recovery of degraded areas, it has the capacity to make high contributions of organic matter via leaf litter, retranslocates nutrients and has high efficiency in the use of nutrients.